Experimental Study of Sliding Friction for PET Track Membranes; IOP Conference Series: Materials Science and Engineering; Vol. 125 : Materials Treatment: Current Problems and Solutions - Filippova E. O. Ekaterina Olegovna (2016, 2016)
Title screen